Traumatic skull fractures in dogs and cats: A comparative analysis of neurological and computed tomographic features. (20th July 2020) - Amengual‐Batle, Pablo; José‐López, Roberto; Durand, Alexane; Czopowicz, Michal; Beltran, Elsa; Guevar, Julien; Lazzerini, Kali; De Decker, Steven; Muñana, Karen; Early, Peter; Mariani, Christopher; Olby, Natasha; et al.
Abstract: Background: Traumatic skull fractures (TSF) are relatively frequent in dogs and cats, but little information is available regarding their clinical and imaging features. Hypothesis/Objectives: To describe the neurological and computed tomographic (CT) features of a large cohort of dogs and cats with TSF. Animals: Ninety‐one dogs and 95 cats with TSF identified on CT. Methods: Multicenter retrospective comparative study. Signalment, cause of trauma, fracture locations and characteristics, presence of neurological deficits, and 1‐week survival were recorded. Fractures were classified according to the extent of fragmentation and displacement. Results: The cranial vault was affected more frequently in dogs ( P = .003), whereas the face and base of the cranium more often was affected in cats ( P  < .001). Cats presented with multiple fractures more frequently ( P  < .001). All animals with TSF in the cranial vault were more likely to develop neurological signs ( P = .02), especially when depressed fractures were present (95% confidence interval [CI], 1.7‐8.2; P = .001). Animals with TSF located only in the facial region were less likely to have neurological signs (odds ratio with Mantel‐Haenszel's method [ORMH ], 0.2; 95% CI, 0.1‐0.6; P = .004). Most affected animals (84.9%) survived the first week post‐trauma. Death was more likely with fractures of the cranial vault ( P = .003), especially when fragmented ( P = .007) and displaced ( P = .004). Conclusions and Clinical Importance: Traumatic skull fracture distribution and patterns are different between dogs and cats. Cranial vault fractures were associated with neurological deficits and worse survival. The presence of TSF alone should not be considered a negative prognostic factor because most affected animals survived the first week.